Indexes to Debates of the House of Assembly (Hansard) - South Africa Parliament, House of Assembly; South Africa Parliament (Cape Town Government Printers, 1974)
South Africa Parliament House of Assembly. Debates of the House of Assembly (Hansard). Debates of Standing Committees published.
Merged with: Debates of the House of Delegates, and; Debates of the House of Representatives, to form: Debates of Parliament. Debates of Standing Committees published annually and parallel with Afrikaans title. 139 v. 22 cm.
Keywords: Indexes to Debates; House of Assembly; First Session; Fifth Parliament; 1974; ISBN 0621018821; JC045348; Vol. 54; Hansard; Index to Questions